ESTIMASI SERAPAN KARBON DAN NILAI JASA LINGKUNGAN PADA HUTAN MANGROVE BLOK JATI PAPAK TAMAN NASIONAL ALAS PURWO - Firmansyah, Moh. (JURNAL BIOSENSE, 2025)
Global warming is a critical issue currently faced worldwide, primarily driven by the increase in greenhouse gas emissions resulting from the combustion of fossil fuels due to human activities. Mangrove ecosystems play a vital role in mitigating climate change by absorbing carbon dioxide. Alas Purwo National Park is one of the habitats with a promising ecosystem for carbon sequestration. This study aims to examine the carbon sequestration potential and the environmental service value of mangrove trees in Alas Purwo National Park. A non-destructive, non-harvesting method was employed, with data collected using the quadrant transect method that spanned from the back zone to the front zone of the mangrove area. Five plots measuring 20 x 20 meters were established at each sampling station. Carbon analysis was conducted using an allometric equation approach to estimate the aboveground biomass (AGB). The results showed that the total mangrove carbon stock in Alas Purwo National Park, specifically aboveground carbon, amounted to 4.604,373 tons per hectare. The total value of the environmental services provided was estimated at IDR 1,128,232.11. Sonneratia alba contributed the highest carbon stock, reaching 367.806 per individual, while Ceriops tagal contributed the lowest, at only 6.172. Based on these findings, there is a need for continued conservation efforts of the mangrove ecosystem, enhancement of carbon sequestration potential, and strengthened climate change mitigation strategies.